Acoustic emission : methodology and application - Nazarchuk, Zinoviĭ Teodorovich; Skal's'kyj, Valentyn Romanovyč 1954-; Serhiyenko, Oleh (Cham, Switzerland : Springer, 2017)
This monograph analyses in detail the physical aspects of the elastic waves radiation during deformation or fracture of materials. It presents themethodological bases for the practical use of acoustic emission device, anddescribes the results of theoretical and experimental researches of evaluation of the crack growth resistance of materials, selection of theuseful AE signals. The efficiency of this methodology is shown through the diagnostics of various-purpose industrial objects. The authors obtainresults of experimental researches with the help of the new methods andfacilities.
Keywords: EMISIÓN ACÚSTICA; INGENIERÍA ACÚSTICA